Analysis of Live Music, Taste, and Product Diversity on Customer Satisfaction at Parewa Coffee Padang - Yuni Candra; Mira Despika; Hafrizal Okta Ade Putra; Rahmat Rahmat (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of live music, taste and product variety on customer satisfaction at Parewa Coffee Padang. The research method used is descriptive quantitative. The sample in this study amounted to 100 respondents, with purposive sampling technique. The data analysis technique used is multiple linear regression, t test, f test, and the coefficient of determination. The results of the t-test were carried out partially with the live music variable, taste and product variety having a significant effect on Parewa Coffee customer satisfaction. the results of the f test variable live music, taste and product variety have a significant effect on customer satisfaction Parewa Coffee, while the results of the coefficient of determination are found in the Adjusted R-Square value of 23.0%